Empathy Variation in General Practice: A Survey among General Practitioners in Denmark - Charles, Justin A. (Int J Environ Res Public Health, 2018)
Background: Previous studies have demonstrated that high levels of physician empathy may be correlated with improved patient health outcomes and high physician job satisfaction. Knowledge about variation in empathy and related general practitioner (GP) characteristics may allow for a more informed approach to improve empathy among GPs. Objective: Our objective is to measure and analyze variation in physician empathy and its association with GP demographic, professional, and job satisfaction characteristics. Methods: 464 Danish GPs responded to a survey containing the Danish version of the Jefferson Scale of Empathy for Health Professionals (JSE-HP) and questions related to their demographic, professional and job satisfaction characteristics. Descriptive statistics and a quantile plot of the ordered empathy scores were used to describe empathy variation. In addition, random-effect logistic regression analysis was performed to explore the association between empathy levels and the included GP characteristics. Results: Empathy scores were negatively skewed with a mean score of 117.9 and a standard deviation of 10.1 within a range from 99 (p5) to 135 (p95). GPs aged 45–54 years and GPs who are not employed outside of their practice were less likely to have high empathy scores (≥120). Neither gender, nor length of time since specialization, length of time in current practice, practice type, practice location, or job satisfaction was associated with odds of having high physician empathy. However, odds of having a high empathy score were higher for GPs who stated that the physician-patient relationship and interaction with colleagues has a high contribution to job satisfaction compared to the reference groups (low and medium contribution of these factors). This was also the trend for GPs who stated a high contribution to job satisfaction from intellectual stimulation. In contrast, high contribution of economic profit and prestige did not contribute to increased odds of having a high empathy score. Conclusions: Albeit generally high, we observed substantial variation in physician empathy levels among this population of Danish GPs. This variation is positively associated with values of interpersonal relationships and interaction with colleagues, and negatively associated with middle age (45–54 years) and lack of outside employment. There is room to increase GP physician empathy via educational and organizational interventions, and consequently, to improve healthcare quality and outcomes.